Estimation of hazen williams’s constant for a residential water distribution network; GMDH and PSO approach - kumar Tyagi, Dharmendra; Majumder, Mrinmoy; Kant, Chander; Prabhat Singh, Ashish (International Journal of Engineering and Technology, 2018)
Hazen-William equation is used to estimate the Fluid flow in closed channel. There are various models for estimation of pipe flow, however the accuracy and reliability of models varies due to the empirical nature of the Hazen-William constant .the applicability of model also become constrained due to the dependency of constant on pipe material, dimension and flow potential. Different type of pipeline arranged in different Networks will require different value of the constant and is generally retrieved from the data collected for the pipe network. The case dependency of the model has makes the model erroneous and often subjective that is why the present study tries to propose a model which can be used for any network where the output will depend upon the inputs. In this aspect the soft computation techniques: - GMDH and PSO was utilized in an unconventional way to establish the value of CHW =f (H, L, V, D).Â According to result the GMDH becomes the better model than the PSO where the accuracy is about 76.315%.Â